Mild Encephalitis/Encephalopathy with a Reversible Splenial Lesion Associated with Rhinovirus Infection - N Zafer Kurugol; Sule Gokce; Cenk Eraslan; E Ulas Saz; Sirmen Kizilcan; M Ozgur Cogullu (Journal of Vaccines and Immunology - Peertechz Publications, 2015)
We report a 7-year-old patient with mild encephalopathy with a reversible splenial lesion (MERS) presenting with recurrent delirious behavior, hallucinations and seizures following common cold. Cranial MRI showed high signal intensity in the splenium of the corpus callosum. Rhinovirus was detected in the nasopharyngeal swab by multiplex PCR. Other respiratory viruses were not detected. Microbiologic tests for Epstein-Barr virus, herpes simplex virus, varicella-zoster virus, cytomegalovirus, measles, mumps, rubella and  ycoplasma pneumoniae were also negative. This is the first reported case ofMERS associated with rhinovirus infection.